Records management practices of colleges of education in Nigeria: a study of federal college of education, Yola and college of education, Jalingo (2004)
Records are information, irrespective of the format on which they appear Records are important. Without records, an organization simply cannot function. It is in the light of this that this study examined records management practices in the studied institutions to determine their relevance and effectiveness in facilitating the implementation of the aims and objectives of the Colleges. Findings from the study revealed that the studied institutions applied the records life - cycle concept in the management of records but without putting a functional records management practices in place. The study recommended that functional records management should be implemented especially in the areas of recruiting professionally trained personnel in the management of records, improved storage facilities, automation of records and putting in place a disaster management programme as a security measure to guide against natural and man-made disaster among others.